Simulating climate change impact on rice yield in different agroclimatic zones of Kerala using CERES- rice model - Harithalekshmi V.,; B. Ajithkumar, (Annals of Agricultural Research, 2024)
The likely effects of climate change, caused by increasing temperature and carbon dioxide concentration on rice yield were evaluated using CERES rice model in five agro climatic zones of Kerala. Since increasing trend of temperature and carbon dioxide is anticipated in future, this study simulated yield under three condition viz., elevated temperature, elevated carbon dioxide and combination of both. The results suggested that temperature has a detrimental influence where as carbon dioxide has an augmenting influence on rice yield. Combined effect of these factors suggested that the yield was found to increase under increasing CO2 concentration when the elevation in temperature was 1 oC, but under the temperature rise of 2-4 oC yield reduced irrespective of the increased concentration of CO2 in all agro climatic zones.